The Effectiveness of Mobile Application-Based Micro-Meditation in Reducing Students’ Academic Stress - Arshaka, Arshaka; Chokri, Baldwin; Rakhsan, Rakhsan (PELNUS | Pen en Light for Natural Union of Science, 2025)
The Effectiveness of Mobile Application-Based Micro-Meditation in Reducing Students’ Academic Stress Academic stress has become a significant challenge for students, affecting their mental health, concentration, emotional regulation, and academic performance. This study aims to examine the effectiveness of mobile application-based micro-meditation in reducing academic stress among university students. A quasi-experimental pretest-posttest design was employed, involving students aged 18–25 years who engaged in daily, 5–10 minute guided meditation sessions via a mobile application for four weeks. Academic stress levels were measured using the Perceived Stress Scale (PSS) and the Academic Stress Inventory before and after the intervention. The results indicated a significant reduction in perceived academic stress, alongside improvements in concentration, emotional regulation, and academic performance. Furthermore, the effectiveness of the intervention was influenced by the frequency of use and engagement level, with students who practiced consistently and attentively experiencing the most substantial benefits. These findings suggest that mobile micro-meditation is a practical, accessible, and time-efficient strategy for managing academic stress, offering valuable insights for educators, counselors, and universities seeking scalable mental health interventions.